Lactobacillus plantarum Alleviates Obesity by Altering the Composition of the Gut Microbiota in High-Fat Diet-Fed Mice - Ma, Yong; Fei, Yanquan; Han, Xuebing; Liu, Gang; Fang, Jun (Frontiers in Nutrition, 2022)
Obesity is usually accompanied by metabolic disorders and intestinal flora imbalance. Due to its diverse biological activities, Lactobacillus Plantarum is widely used to alleviate various diseases as a probiotic. Here, we show that Lactobacillus Plantarum can reduce the body weight of mice fed high-fat diets, reduce fat accumulation, and enhance mice glucose tolerance. Our results show that Lactobacillus Plantarum can significantly reduce the expression of DGAT1 and DGAT2, increase the expression of Cpt1a, and promote the process of lipid metabolism. Further data show that Lactobacillus Plantarum can not only increase the SCFAs content in the colon, but also reverse the intestinal flora disorder caused by HFD, increase the abundance of Bacteroides, and Bifidobacteriales, and reduce the abundance of Firmicutes and Clostridiales. Finally, through Pearson correlation analysis, we found that Bacteroides and SCFAs are positively correlated, while Clostridiales are negatively correlated with SCFAs. Therefore, we believe that Lactobacillus Plantarum can regulate the structure of the intestinal microbial community, increase the production of SCFAs and thus regulate lipid metabolism.